Analysis of Learning Environment Survey at State Islamic Primary School - Nurnada Anggraini; Misbahul Jannah (Indonesian Journal of Education and Social Humanities, 2024)
The student's learning environment is very important in the learning process. A good student learning environment will create comfort for student activities in every learning process. A learning environment survey is needed to measure the quality of input and learning processes in the classroom and in educational units in accordance with the learning environment intended in the National Assessment. The aim of this research is to describe the learning environment for State Islamic Primary School 39 Aceh Besar students. This research method is survey research with a qualitative descriptive approach. Research instruments include observation, interviews and documentation. This research is population research where all objects are respondents in the research. School environment, facilities and infrastructure, and all classrooms of State Islamic Primary School 39 Aceh Besar. The research results show that the analysis of the learning environment in schools based on survey results shows that teachers have succeeded in creating a classroom atmosphere that is conducive to students not feeling bored and bored, good classroom management coupled with the addition of facilities and infrastructure. Based on a survey of the family environment of students at State Islamic Primary School 39 Aceh Besar, there is still a lack of attention from families, especially parents, in encouraging student learning outside of school. Students are still less educated, such as students who are lazy, such as spending time watching TV, not following their parents' orders to study and playing a lot outside the house. Based on a survey of the community environment, students at State Islamic Primary School 39 Aceh Besar still do not support it. There are still students who are undisciplined and lack supervision. Students lack parental attention and tend to misbehave.